Current and Potential Therapies Targeting Inflammation in NASH - Albhaisi, Somaya; Noureddin, Mazen (Frontiers in Endocrinology, 2021)
Nonalcoholic steatohepatitis (NASH) is the advanced form of nonalcoholic fatty liver disease (NAFLD). It is characterized by hepatic steatosis, inflammation, hepatocellular injury, and fibrosis. Inflammation plays a key role in the progression of NASH and can be provoked by intrahepatic (e.g., lipotoxicity, immune responses, oxidative stress and cell death) and extrahepatic sources (adipose tissue or gut). The identification of triggers of inflammation is central to understanding the mechanisms in NASH development and progression and in designing targeted therapies that can halt or reverse the disease. In this review, we summarize the current and potential therapies targeting inflammation in NASH.